Financial inclusion, financial literacy, and financial education in Georgia - Yaroslava Babych; Maya Grigolia; Davit Keshelava (Asian Development Bank Institute (ADBI), 2018)
In this paper, we provide a comprehensive overview of the current state of financial inclusion and financial literacy in Georgia based on the latest literature, statistical evidence, and recent surveys. The paper reviews current government policy initiatives and strategy documents aimed at improving financial access of SMEs and households; analyzes the state of the regulatory framework in Georgia; focuses on the causes behind the current low levels of financial inclusion and financial literacy among the young, the poor, and the rural population; and provides policy recommendations to comprehensively address the financial inclusion problem in Georgia.
Keywords: G20; G21; G23; G28; 330; economic development; financial stability; financial literacy; financial inclusion; financial education